Perspectives on the utilization of Aegilops species containing the U genome in wheat breeding: a review - Badaeva, Ekaterina D.; González Franco, Maida Jazmin; Razumova, Olga; Tereshchenko, Nadezhda A.; Divashuk, Mikhail (Frontiers in Plant Science, 2025)
The genus Aegilops L. is the closest wild relative of wheat (Triticum L.), which contributed two of the three genomes to cultivated wheat. The genus Aegilops comprises 23 species differing in ploidy level and genome composition; diploid species possess the C, D, M, N, S, and U genome types, whereas various genome combinations are identified in tetraploid and hexaploid forms. The U genome is present in diploid Ae. umbellulata and eight polyploid species [Ae. triuncialis, Ae. biuncialis, Ae. geniculata, Ae. peregrina, Ae. kotschyi, Ae. columnaris, Ae. neglecta (4× and 6×), and Ae. juvenalis]. Some of these species have a wide distribution range, resulting in high adaptive capacity to various environmental conditions, and can serve as a valuable source of genetic diversity and useful genes for wheat breeding. The U genome is substantially rearranged relative to the genomes of common wheat, which hampers the direct transfer of useful traits from Aegilops to wheat. However, many genes conferring resistance to leaf rust (Lr9, Lr76, Lr57, Lr54, Lr59, Lr58), stripe rust (Yr70, Yr40, Yr37, Yr42), stem rust (Sr53), nematodes (CreX, CreY, Cre7), and various abiotic stresses have been successfully introgressed from Aegilops into the wheat genome. In this review, we describe the status of the contribution of Aegilops species carrying the U genome to wheat improvement, the methods used by different scientific teams to transfer genetic material, and the future prospective of exploitation of their useful traits in practical breeding.